“Unraveling the Clot-Miscarriage Nexus: Mechanisms, Management, and Future Directions in Thrombosis-Related Recurrent Pregnancy Loss” - Ahmed Hussein BSc; Amin Solouki PhD; Niloofar Pilehvari MS; Fatemeh Sotudeh Chafi MS; Hanieh Noormohamadi MS; Parvaneh Abbasi Sourki PhD; Athena Behforouz MD; Hamed Soleimani Samarkhazan PhD (Clinical and Applied Thrombosis/Hemostasis)
Recurrent spontaneous abortion (RSA) is a multifactorial condition influenced by genetic, hormonal, immunological, and anatomical factors. Thrombophilia, characterized by a heightened propensity for blood clotting, is a significant contributor to RSA. This review examines the mechanisms connecting thrombosis and RSA, focusing on hypercoagulable states, placental thrombosis, inflammation, and endothelial dysfunction. Genetic and acquired thrombophilic factors, such as factor V Leiden mutation, prothrombin gene mutation, protein C and S deficiencies, antithrombin III deficiency, antiphospholipid syndrome, and hyperhomocysteinemia, are discussed in detail. The diagnosis of thrombophilia in RSA entails a comprehensive clinical evaluation, including the assessment of physical examination, medical history and laboratory investigations, although there is still debate over the need for universal screening. Therapeutic strategies, including anticoagulant and antiplatelet therapies, as well as lifestyle modifications, are tailored to individual risk factors and disease severity. Although anticoagulant therapy demonstrates potential in lowering the risk of miscarriage, additional research is necessary to refine treatment protocols and assess long-term outcomes. This review highlights the need for a nuanced approach to managing thrombophilia-associated RSA, balancing diagnostic precision with therapeutic efficacy to improve reproductive outcomes.